(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Arthur Miller was one of the leading Americanplaywrights of the twentieth century. Miller wrote Death of a Salesman, whichwon the Pulitzer Prize and transformed Miller into a national sensation. Manycritics described Death of a Salesman as the first great American tragedy, andMiller gained eminence as a man who understood the deep essence of the UnitedStates. Death of a Salesman was first produced on Broadway on Feb 10, 1949. Theplay has been studied generally in terms of a commentary on the failure of theAmerican Dream. Willy Loman has generally been regarded as a victim of theAmerican society. But this paper attempts to study Willy Loman’s character notas a victim either of American dream or of the society but as a man who himselfis responsible for his failure for not realizing his own nature as well as thenature of his dreams. He deceives himself and lives in ‘bad-faith’.